Pengaruh Preferensi Konsumen, Digital Marketing, dan Lifestyle terhadap Keputusan Pembelian Pada Cafe Edelweiss Wonokitri, Pasuruan - Nur Rokhmad Nuzil; Nofan (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This study aims to comprehensively analyze the influence of consumer preferences, digital marketing, and lifestyle on purchasing decisions. The research employs a quantitative approach using multiple linear regression analysis to determine the relationships among these variables. Data was meticulously collected through well-structured questionnaires distributed to a diverse group of respondents who had recently made purchases, ensuring a broad representation of consumer behavior. The analysis results indicate that the variables of consumer preferences, digital marketing, and lifestyle each have a positive and statistically significant effect on purchasing decisions. Specifically, consumer preferences play a pivotal role in shaping purchasing behavior, while digital marketing efforts effectively reach and engage target audiences. Additionally, lifestyle alignment with consumer trends further enhances the likelihood of purchase decisions. These findings suggest that businesses aiming to improve their sales performance should focus on enhancing consumer preferences through personalized offerings, employing effective digital marketing strategies that resonate with target audiences, and aligning products and services with the relevant consumer lifestyles. In conclusion, consumer preferences, digital marketing, and lifestyle are critical factors that businesses should strategically consider when developing comprehensive and effective marketing strategies to boost purchasing decisions and achieve sustained growth.